Evaluation and Improvement of Manufacturing System Using Computer Software Arena - Mohammed Hasan, Kawthar A.; Kadhum, Ali H.; Morad, Ameer H. (Al-Khwarizmi Engineering Journal, 2019)
The main purpose of the paper is to identify the controllability of an existing production system; yogurt production line in Abu Ghraib Dairy Factory which has several machines of food processing and packing that has been studied. Through the starting of analysis, instability in production has been found in the factory. The analysis is built depending on experimental observation and data collection for different processing time of the machines, and statistical analysis has been conducted to model the production system. Arena Software is applied for simulating and analyzing the current state of the production system, and results are expanded to improve the system production and efficiency. Research method is applied to contribute in knowing and expecting the future running of the system to enhance the controllability of the system production and improve the production system and machine efficiency. Moreover, built an experiment-real model in Arena in order to control the system in term of production and process. First step is to collect the statistical data required for analysis in terms of input and output data for analysis. Second, is to track the production problem in term of process bottleneck in order to improve the utilization of the system. Third is to validate the model in order to overcome the product demand of the system uncontrollability. Through the result analysis of waiting time and production rate, it is clearly shown that system is stable with a need to resetting the capacity as a chance for the improvement, regarding to resources utilization. Re-planning resources capacity positively enhances the production and profitability of the system.